1976
DOI: 10.1128/aac.9.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of Sisomicin

Abstract: An antibody induced in rabbits against a gentamicin-bovine serum albumin conjugate cross-reacted with the chemically related aminoglycoside, sisomicin, facilitating the development of a sisomicin radioimmunoassay. Sisomicin was labeled with 12'5 using an acylating agent [3-(4-hydroxyphenyl)propionic acid-N-hydroxy-succinimide ester]. The resulting assay produced a linear standard curve on a logit-log plot with a sensitivity of 140 pg. Comparison with a microbiological assay showed no significant difference (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the microbiological assay, the agar well diffusion method was used and Klebsiella was set as the test organism. The result of radioimmunoassay showed the sensitivity as 140 pg/mL and in comparison with the microbiological assay, there were not significant differences [77] Microbiological and instrumental methods have been used to determine the amount of sisomicin, and the biosensor method has been compared with the microbiological method. There are good instrumental methods for evaluation of sisomicin in the clinical monitoring and food industry and maybe the microbiological method could be used instead of chemical methods in any laboratories.…”
Section: Sisomicinmentioning
confidence: 99%
“…In the microbiological assay, the agar well diffusion method was used and Klebsiella was set as the test organism. The result of radioimmunoassay showed the sensitivity as 140 pg/mL and in comparison with the microbiological assay, there were not significant differences [77] Microbiological and instrumental methods have been used to determine the amount of sisomicin, and the biosensor method has been compared with the microbiological method. There are good instrumental methods for evaluation of sisomicin in the clinical monitoring and food industry and maybe the microbiological method could be used instead of chemical methods in any laboratories.…”
Section: Sisomicinmentioning
confidence: 99%
“…Recent work has shown the usefulness of cross-reacting gentamicin antisera for dual use in an RIA for sisomicin (3). This novel use of cross-reacting antisera was primarily due to the reported 65% cross-reaction of gentamicin antisera with sisomicin.…”
mentioning
confidence: 99%
“…Proline and hydroxy proline do not react with the OPA reagent. However, Roth (55) reported that the c. Radioimmuno assay Radioimmuno assays are sensitive techniques for determining aminoglycoside antibiotic concentrations (119)(120)(121)(122)(123)(124). The theory of radioimmuno assays will not be discussed here, as an excellent review is presented by Chalt and Ebersole (125).…”
Section: N-r + Zhgomentioning
confidence: 99%